THE TEACHING OF FIGHTS IN SCHOOL PHYSICAL EDUCATION: A STATE OF KNOWLEDGE OF BRAZILIAN STUDIES - Carla da Silva Ferreira; Nicole Marceli Nunes Cardoso; Tiele Neto Cardoso; Flávio Py Mariante Neto; Daniel Giordani Vasques (Journal of Physical Education)
ABSTRACT This article aims to analyze the Brazilian academic publications on fights and Physical Education. We used content analysis through a state of knowledge, with 38 articles as corpus. As results we built four empirical analytical categories: 1) Space and sociocultural aspects: they point the lack of infrastructure and the scarcity of materials as restrictive factors for the approach of the fight contents in schools; 2) Technologies/media: that serve as auxiliary tools for the inclusion of fights in school Physical Education; 3) Physical Education curriculum: addresses issues related to content, culture, documents and teachers; and 4) Pedagogical practice: which involves more specific issues observed in the studies, such as methodologies involving the application of the content to classes, experiences, dimensions of the content, activities and implications about the themes discussed in the content, such as the association with violence, gender discrimination and sexuality. We conclude that the studies show that the approach of fights as content in schools is still incipient, being the insecurity of the teacher a preponderant factor so that fights are not inserted. Thus, studies indicate the need to create materials and methodologies that help teachers, thus enabling the use of content already consolidated in the literature.